‘Boating’ out migrated dexamethasone implant; surgical management of removal of anterior chamber migrated dexamethasone intravitreal implant : a case report - Teo, BH; Safinaz Mohd Khialdin,; Mae-Lynn Catherine Bastion,; Amin A,; R, Edward; Mushawiahti Mustapha, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
It is rare for anterior chamber migration of an Ozurdex® implant from vitreous cavity, but it is seen more frequently in aphakic eyes or in pseudophakic cases with zonular dehiscense. We describe a case of a middle-aged gentleman who had persistent diabetic macular oedema not responding to anti-VEGF (vascular endothelium growth factor), who was treated with intravitreal Ozurdex® in his post vitrectomized eye and developed anterior migration of the implant to the anterior chamber. Anterior dislocation of an intravitreal implant of dexamethasone can be managed by repositioning it to the vitreous cavity or removing it through a corneal limbal incision. Ozurdex® is a friable implant, especially after a few weeks of implantation. Therefore, removal of the implant by grasping or aspiration may lead to its fracture or dispersion of the implant material. This is a report of a simple,fast and effective technique to remove a migrated Ozurdex® from the anterior chamber using a modified silicone tip.